The Waste Management Policy - Frhendy Aghata; Nico Fajar Maulana (Sahwahita: Community Engagement Journal, 2023)
The issue of waste management is presently a multifaceted challenge, necessitating a comprehensive approach for effective resolution. The waste management policy encompasses various levels of governance, including laws, government rules, regional regulations, and governor regulations. In line with this, Pangsan Village has developed village regulations pertaining to trash management. The prevailing technique in waste management involves a sequential progression from upstream to downstream. The implementation of an upstream strategy has been observed in Pangsan Village with the adoption of certain village ordinances pertaining to cleanliness, aesthetics, organisation, and environmental well-being. Nevertheless, the current state of waste management remains suboptimal due to the absence of regulations mandating garbage sorting by dealers, markets, and workshops. Similarly, the current downstream strategy is suboptimal due to the lack of waste bank regulation in the draught. However, this issue can be addressed by enhancing the draught village laws or by implementing a decision made by the village head.